2020
DOI: 10.1001/jama.2019.20675
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes Through 5 Years for Active Surveillance, Surgery, Brachytherapy, or External Beam Radiation With or Without Androgen Deprivation Therapy for Localized Prostate Cancer

Abstract: IMPORTANCE Understanding adverse effects of contemporary treatment approaches for men with favorable-risk and unfavorable-risk localized prostate cancer could inform treatment selection. OBJECTIVE To compare functional outcomes associated with prostate cancer treatments over 5 years after treatment. DESIGN, SETTING, AND PARTICIPANTS Prospective, population-based cohort study of 1386 men with favorable-risk (clinical stage cT1 to cT2bN0M0, prostate-specific antigen [PSA] Յ20 ng/mL, and Grade Group 1-2) prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
220
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 210 publications
(240 citation statements)
references
References 41 publications
14
220
2
4
Order By: Relevance
“…These results are consistent with findings from studies evaluating shorter term quality of life in patients with localised prostate cancer. 6 34 …”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with findings from studies evaluating shorter term quality of life in patients with localised prostate cancer. 6 34 …”
Section: Discussionmentioning
confidence: 99%
“…It is therefore essential to have robust information about the long-term effects on urinary, bowel, hormonal, and sexual function. Few studies report long-term prospectively collected health-related quality of life (HRQoL) longitudinal data [ 3 , 4 , 5 , 6 ].…”
Section: Purposementioning
confidence: 99%
“…8,9 Although PB is curative for prostate cancer, a previous study showed that high radiation doses to the pelvic tissues or structures increased the risk of hematuria, urinary incontinence, rectal injury and ED. 10 However, it currently remains unclear whether high-dose radiation to the prostate and surrounding tissues induces EF deterioration after PB. Merrick et al reported that excessive radiation to the prostate or penile bulb was closely associated with the preservation of potency after PB.…”
Section: Introductionmentioning
confidence: 99%